Stimulator of Interferon Genes (STING) Promotes Staphylococcus aureus-Induced Extracellular Traps Formation via the ROS-ERK Signaling Pathway - Liu, Zhen-Zhen; Chen, Wei; Zhou, Cheng-Kai; Ma, Ke; Gao, Yu; Yang, Yong-Jun (Frontiers in Cell and Developmental Biology, 2022)
Stimulator of interferon genes (STING) is a cytosolic DNA sensor or directly recognizes bacterial cyclic dinucleotides, which is required for the detection of microbial infection. Extracellular traps (ETs) are known to be part of the antimicrobial defense system. However, the implication of STING in ETs formation during microbial infection remains unknown. Here, we showed that STING contributed to Staphylococcus aureus (S. aureus)-induced ETs formation through the ROS-ERK signaling. STING deficiency exhibited decreased cell-free DNA (cfDNA) level, reduced expression of citrullinated histone H3 (CitH3), and diminished DNA colocalization with CitH3 and myeloperoxidase (MPO). Interestingly, NADPH oxidase-derived reactive oxygen species (ROS) promoted ETs formation, accompanied by increased activation of extracellular signal-regulated kinase 1 and 2 (ERK1/2) in S. aureus-stimulated bone marrow-derived macrophages (BMDMs). Corresponding to less ROS production, decreased ERK1/2 activation was shown in STING-/- BMDMs after S. aureus infection. Importantly, inhibiting the ROS-ERK signal reduced the ETs formation and the differences disappeared between WT and STING-/- BMDMs after S. aureus infection. Moreover, STING-/- BMDMs exhibited significantly increased levels of extracellular bacteria compared to WT BMDMs regardless of phagocytosis. In addition, such differences disappeared after DNase I treatment. DNase I treatment also facilitated pathogen colonization without affecting the inflammatory cells infiltration and pro-inflammatory factors secretion following pulmonary S. aureus infection. Furthermore, STING-/- mice presented decreased levels of cfDNA and CitH3, along with increased bacterial colonization compared to WT mice. Altogether, these findings highlighted that STING promoted ETs formation via the ROS-ERK signal for host defense against S. aureus infection.